2010
DOI: 10.1124/dmd.110.033613
|View full text |Cite
|
Sign up to set email alerts
|

Drug Efflux Transporter Multidrug Resistance-Associated Protein 5 Affects Sensitivity of Pancreatic Cancer Cell Lines to the Nucleoside Anticancer Drug 5-Fluorouracil

Abstract: ABSTRACT:Pancreatic adenocarcinoma is one of the malignancies that is highly resistant to therapy and among the leading causes of cancer-related death. Several factors may influence pancreatic cancer resistance, and expression of ATP-binding cassette transport proteins is one of the major mechanisms of drug resistance. Members of this family's C-branch, also referred to as multidrug resistanceassociated proteins (MRPs), might be of particular interest be-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…Therefore, amino acid and dipeptide prodrugs of chemotherapeutic agents might have another advantage transporting drugs into cancer cells via influx transporters such as LATs, and PEPTs except ENTs [7,11,16,87]. It has been reported that the chemoresistance is attributed to the up-regulation of MRPs, especially MRP5 [80,81,88,89,90]. Numerous studies have been conducted to overcome this resistance to treat cancers but clinically successful approaches have not been established [91,92,93,94,95].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, amino acid and dipeptide prodrugs of chemotherapeutic agents might have another advantage transporting drugs into cancer cells via influx transporters such as LATs, and PEPTs except ENTs [7,11,16,87]. It has been reported that the chemoresistance is attributed to the up-regulation of MRPs, especially MRP5 [80,81,88,89,90]. Numerous studies have been conducted to overcome this resistance to treat cancers but clinically successful approaches have not been established [91,92,93,94,95].…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells are more dependent on the glycolytic pathway for ATP generation, compared with normal cells, and they eventually acquire drug resistance, typically due to the aberrant expression of drug-expelling ABC transporters (12). The ATP-dependence of drug transporters for activity (40,41) suggests that glycolysis inhibition may increase the concentration of chemotherapeutic agents in cancer cells (42,43). The most widely studied transporters, including MRP1, BCRP and P-gp, are able to transport a variety of structurally-unassociated chemotherapeutic compounds from cancer cells, thereby inducing MDR (44).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, such MRP5-silenced Capan-1 cells in which MRP5 mRNA expression was downregulated to about 25% of that in control cells [26] showed an increased sensitivity to 5-FU as compared to parental or vector-transfected Capan-1 cells (Table 1) [26]. The contribution of MRP5 to 5-FU resistance was confirmed in a more recent study using Patu-02 pancreatic cancer cells where knock down of MRP5 also significantly increased cellular cytotoxicity of 5-FU [76]. …”
Section: Resultsmentioning
confidence: 89%